Gagasan Dan Manifestasi Modernisasi Pesantren A.S Panji Gumilang Di Ma’had Al-Zaytun - Sarno Hanipudin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: This paper learn and find to progress steps from Ma’had Al- Zaytun Islamic boarding school for develop it that have an international level. This finding is gotten after through a research of mechanism that is difficult and also through a protective guide when interview with A.S. Panji Gumilang. This research shows that basic a Islamic boarding school have to able to read to real and answer to challenge of periods, so the modern in some part have to do, as a maintenance, a payment, a management, also a vision and orientation. Keywords : The Modern Islamic Boarding School, Ma’had Al- Zaytun.